Autism : educational and therapeutic approaches - Kalyva, Efrosini. 4 0 16; 5 (Los Angeles : SAGE, 2011)
There are a number of different approaches and therapies available for children, young people and adults on the autistic spectrum. This work offers concise and clear explanations of a variety of proposed interventions and their effectiveness, and helps the reader to decide on the most appropriate treatment for each individual. The author provides information about recent scientific evidence and the latest research, and allows the reader to consider the pros and cons of each approach. She focuses on the following areas: cognitive-behavioral approaches; developing social interaction; alternative communication strategies; developing play; sensory-motor approaches; psychotherapeutic approaches; biochemical approaches. This guide for practitioners and student teachers provides a comparative examination of the variety of treatments on offer --
Cognitive-behavioural approaches. Applied behaviour analysis ; TEACCH programme ; Cognitive-behavioural therapy ; Denver Health Sciences Programme ; DIR/floortime method ; LEAP: learning experiences: an alternative programme for preschoolers and parents ; Miller method -- Approaches for developing social interaction. Social stories ; Circle of friends -- Approaches for developing alternative communication. PECS ; Sign language -- Approaches based on play. Non-directive play ; Pivotal response training ; Integrated play groups -- Sensorimotor approaches. Music therapy ; Sensory integration ; Auditory integration ; Visual therapies ; Facilitated communication ; Higashi school or Daily Life therapy -- Biochemical approaches. Pharmacotherapy ; Secretin ; Other biochemical therapies -- Other approaches. Psychoanalytic psychotherapy ; Holding therapy ; Son-Rise programme or Options.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Treatment.;Education.;therapy. -- Autism in children;Autistic children;Autism spectrum disorders in children.;Autistic Disorder;Behavior Therapy.;Child.;Education, Special. -- 20; 20; 2